STUDI INFILTRASI DI DAS DUA LAUT KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Nofitasari Nofitasari; Muhammad Ruslan; Syarifuddin Kadir (Jurnal Sylva Scienteae, 2020)
Infiltration is part of the hydrologic cycle, namely the process of entering water from the surface into the soil. Infiltration is affected by vegetation, slope dan soil type. This study aims to analyze the amount of capacity and volume of infiltration in open land, shrubs and rubber plantations in the DAS Dua Laut. The reseach method uses the Horton formula with the observation point using purposive sampling with regard to various land cover and slope classes. The results showed that the highest value of infiltration capacity in rubber plantation land cover at slopes of 0-8% with a value of 1.182 mm/jam and the lowest in open land at slopes of 15-25% with a value of 0.402 mm/jam. The highest infiltration volume value in rubber plantations is 0.734 mm³ while the lowest value in open land is 0.131 mm³. this shows that the higher the slope, the smaller the infiltration and the land that has vegetation the infiltration tends to be greater. The level of slope of the land in the DAS Dua Laut affects the rate of infiltration. Infiltration rate can be categorized as slow and very slow. This is influenced by the type of soil which is clay and dusty clay.Keywords; infiltration; capacity and volume of infiltration; DAS Dua Laut